Effects of rainfall intensity on runoff and sediment yields on bare slopes in a karst area, SW China - Yan, Youjin; Dai, Quanhou; Yuan, Yingfei; Peng, Xudong; Zhao, Longshan; Yang, Jing (Geoderma, 2018)
Due to the impacts of global warming, extreme precipitation events are increasing in frequency and are accelerating the process of rocky desertification in the karst area in southwestern China. In this study, the dual structure of a karst system was simulated in a steel tank, and a rainfall simulation was employed to determine the intensity threshold of erosive rainfall at the surface and the effects of extreme rainfall on runoff generation and sediment yield on karst hillslopes. The results showed the following. i) In order of importance, the factors contributing to runoff were rainfall intensity, slope angle and underground pore fissure degree (UPD), and the factors contributing to sediment yield were rainfall intensity, UPD and slope angle. To cause surface soil erosion, the rainfall intensity had to be >0.8 mm/min. ii) Under light (0.5 mm/min) and moderate rainfall (0.8 and 1.2 mm/min), underground pore fissures are the main pathway for runoff and sediment loss. iii) Under extreme rainfall (1.5 mm/min), surface runoff (and the associated sediment yield) represents the main part of soil erosion on the slope. During such events, the underground erosion proportion is lower, but the underground sediment yield is greater. Because underground pore fissures are the main pathway for underground soil loss, reducing the UPD is an immediate way to prevent and control underground leakage. Engineering measures have the fastest effect, but plant-based measures are more effective and worth popularizing to prevent and control underground soil loss in karst areas. These results provide information significant for controlling rocky desertification and preventing soil erosion in the karst area of southwestern China. [Display omitted] •Erosive rain is ≥0.8 mm/min on limestone hillslopes in the karst area, SW China.•Smaller slope angles are correlated with greater underground soil loss.•The underground soil erosion was easier to be ignored with stronger rainfall.